Pengaruh Cyberloafing Terhadap Kinerja Karyawan melalui Organizational Citizenship Behavior - NUR DIANA, FADIA NUR (Jurnal Ilmu Manajemen (JIM), 2013)
In Using technology employee sometime doing misapplication especially technology internet facility when time work namely cyberloafing .Cyberloafing is counterproductive work behavior can decrease job performance and can also decrease positive behavior that is organizational citizenship behavior. This study aims to examine and analyze whether this study aims to test and analyze whether influence of cyberloafing on job performance and organizational citizenship behavior, and organizational citizenship behavior influence to job performance. The sampling technique of this study is using non probability sampling with sample size of 32 respondents. Statistical analysis method was used Partial Least Square (PLS) with the help of the SMART PLS and SPSS 17.0 software. Based on the result of analysis showed that cyberloafing has negative significant effect on job performance. cyberloafing has negative significant effect on organizational citizenship behavior, and organizational citizenship behavior has positive significant effect on job performance. Keywords: cyberloafing, organizational citizenship behavior, and job performance.